The Role Of Students As Counsellors In Changing The Social Mindset Of Society - Ahmad Muslim (ASTEEC, 2025)
Students, as intellectual individuals who are expected to be able to understand various aspects of life, are also expected to have multitalented abilities. In Wakan Village, which has a strong culture and beliefs and a generally low level of education, people's views on education are often influenced by culture and the assumption that education is not important. This research uses a descriptive qualitative method with a phenomenological approach, and data collection through observation, interviews, and data analysis. The results show that students, as the nation's successors and agents of change, play an important role as counsellors in changing the mindset of parents and society in general. As counsellors, students use various approaches, such as reading sermons, teaching diniyah children, and showing polite attitudes and behaviour. Through these methods, students succeeded in influencing the community and creating positive change, which can be seen in the increasing number of children continuing their education to a higher level, with the full support of their parents and the community as a whole.